Students Experience on Reading Story Book About Medicinal Plants: A Survey Study - Bakti, Temmy Renaldi Setia; Hartati, Tatat; Fuadah, Ulfah Samrotul; Pratama, Sapikzal (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Children's storybooks can provide a variety of information in a series of fantasy stories. One example is health information which contains knowledge about medicinal plants which is packaged with a specific theme according to student interests. However, there are still few students who know about medicinal plants. The research objective was to find out students' experiences about the storybooks they had read, especially about medicinal plants. This research uses a quantitative approach and uses a survey method. A total of 86 students of grade IV SD were selected by random sampling. The results showed that 57% of respondents or as many as 49 students had never read a health-themed storybook containing information about medicinal plants, 34.9% of respondents or 30 students had read it, and 8.1% or seven people. students hesitate. So, from the research data, it can be concluded that there is a need to introduce storybooks about medicinal plants to students.